The IT Governance Measurement using Cobit 5 Framework in Quality Assurance Department - Ali Nurdin; Muharman Lubis (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2023)
This research is conducted to measure and evaluate of IT governance at quality assurance department of XYZ university. The measurement used the COBIT 5 framework by Process Assesment Model. The objective of this research is performing the measurement and evaluation of the IT Governance in the Quality Assurance Division of XYZ University with DSS domains in COBIT 5 Framework. The approach utilized the primer data from interview and questionaire, and secondary data from observation and document stages. The result of this research show the most of the capability level process of IT Governance are at Level 1 (performed) they are 4 processes form DSS domain (DSS01, DSS04, DSS05, DSS06) and at Level 2 (DSS02, DSS03). The conclusion of this research show most of the process perform capability level 1 today.